The Correlation Between Internet-Based Learning and L2 Motivational Self-System - Sakhi Herwiana; Syafi’ul Anam (STAI Miftahul Ula Nganjuk, 2022)
The purpose of this study is to investigate the L2 motivational self-system of English department students, as well as the relationship between e-learning and L2 motivational self-system. The research was carried out at a private university in a small town in East Java, Indonesia. The research design used in this study was quantitative. To collect data from students, the L2MSS and e-learning questionnaires were distributed, and the data was analyzed using the statistical method of Pearson's correlation coefficient. The results show that the instrumentally –promotion sub-factor of students' L2MSS has the highest mean (M = 72.03, SD = 8.87). It means that the students make an effort to achieve their goal of learning English in order to obtain a better job and earn more money in the future. Integrativeness, on the other hand, has the lowest mean (M = 16.25, SD = 1.66), indicating that students put less effort into learning about the culture and art of native speakers of the target language. Furthermore, the Pearson correlation output shows that, despite the moderate correlation, there is a positive correlation between e-learning and L2 motivational self-system. The relationship between internet-based learning and student motivation is an important factor to investigate. Because technology is such an important part of higher education, it is necessary to improve teaching quality. It is suggested that more research be done using a mixed method approach to learn more about the students L2MSS in other areas with different characteristics.